The Relationship Between Family Social Support and The Resilience of Former Drug Addicts - Des Nurmila Sari; Raihanatu Bin qolbi Ruzain; Tengku Nila Fadhlia (Indonesian Journal of Economics, Social, and Humanities, 2023)
The primary purpose of this research is to determine the relationship between family social support and the resilience of former drug addicts. Family social support is a person's perception of the care, appreciation, acceptance, and affection obtained from different people in the surrounding environment. Meanwhile, resilience is a person's ability to endure and not give in to difficult circumstances in his life, as well as trying to learn and be in harmony with those circumstances and then rise to the situation until it becomes better. Citing data from the National Narcotics Agency (BNN) in 2012 shows a surprising fact. Namely, the number of drug abusers in the age group of 10-19 years is 4.4% or around 1 million people. Based on data from the Riau Provins Narcotics Agency (BNP) stated that in drug cases in 2004, Pekanbaru occupied the first level of drug use, reaching 47 cases with narcotics criteria of 30 cases and psychotropics with 17 cases. In this study, the population taken was ex-drug addicts who had completed rehabilitation at the SIKLUS Foundation, Pekanbaru, with a total of 92 people. The sample of this research is former drug addicts at the Pekanbaru Cycle Foundation, with a total of 35 people. The data collected in this study used the social support scale and resilience scale. The sampling technique in this study used the quota sampling method. The results of this study used Pearson product-moment correlation analysis. The analysis showed a positive relationship between family social support and the resilience of the former This means that the higher the social support of the family, the more positive the resilience of former drug addicts. Furthermore, vice versa, the lower the family social support received, the more negative the resilience of former drug addicts. The implication of this study is to give suggestions to parent who has a child who is a drug addict to have some method in psychology to recover from this problem with good social support from family and resilience.